(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2025)
Introduction: Islamic banks seek to balance financial performance with adherence to Sharia principles. Accordingly, this study aimed to identify the impact of applying Islamic accounting standards on Sharia compliance in Yemeni Islamic banks. Methods: The study adopted a descriptive-analytical approach. Data were collected through a questionnaire distributed to a sample of 55 employees working in Yemeni Islamic banks. The data were analyzed using the Statistical Package for the Social Sciences (SPSS), employing descriptive statistics such as means, relative weights, and tests for differences among demographic variables. Results: The findings revealed that the level of application of Islamic accounting standards was high, with a mean score of (3.75) and a relative weight of (74%). The level of Sharia compliance was very high, with a mean score of (4.15) and a relative weight of (83.09%). The results also indicated a significant positive impact of applying Islamic accounting standards on Sharia compliance. No statistically significant differences were found due to demographic variables (educational qualification, specialization, age group, or years of experience), except for the job title variable. Conclusions: The study concluded that the application of Islamic accounting standards effectively enhances Sharia compliance in Yemeni Islamic banks. It recommended strengthening the use of participatory Islamic financing instruments, such as Musharakah and Salam, through staff training and the development of relevant policies and procedures.